Contemporary Interpretive Approaches in Popular Culture Analysis - Jessenia Hayfa Anshara; Ahmad Nurrohim; Andri Nirwana, A.N. (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The study of popular culture is becoming increasingly important in understanding modern social and cultural dynamics. This research will discuss how popular culture influences the formation of identity, values and social interactions in the context of globalization. Popular culture, which includes music, film, television, social media, and fashion, has a significant impact on people's views and behavior. Contemporary interpretive approaches in popular culture analysis use literature study methods to investigate the influence of popular culture in the era of globalization. This method involves an in-depth review of the various related literature, which provides a comprehensive framework for understanding the theoretical basis and previous research on popular culture phenomena. The study highlights the importance of local contexts in interactions with global cultures, resulting in unique cultural hybridity. The research also explores how economic and political forces influence the production and consumption of popular culture and its impact on social structures and power relations. This analysis provides insight into how popular culture not only reflects but also influences social values and norms, as well as how people adapt and shape their identities. In conclusion, popular culture plays a key role in the formation and change of social values, and influences power dynamics and social structures, both in global and local contexts.